The evaluation of International Health Regulations 2005 application in Mukdahan and Ubonratchathani Province - ลิมปวิทยากุล มนัสนันท์; เขั้อลี เสถียร; ครองใจ วัชรชัย (Disease Control Journal, 2013)
This Study has aims to evaluate the implementation of the rules of International Health Regulations 2005 (IHR 2005) in the provinces bordered Thailand - Loas and Cambodia, namely, Mukdahan Province and Ubonratchthani. Data collection was done during July - October 2012 by documentary review and indept interview 26 of the involved officers. The results revealed that the policy on IHR 2005 was recognized and transferred among the officers in the organizations of The Department of Disease Control only. The disease surveillance and investigation in all level are able to perform effectively while the preparedness and emer¬gency response were well practiced in the provincial level. However, the gaps of surveillance system were found in the private sectors and in the district and sub-district level where faced with insufficient of staffs and lack of experience. The disease control port entry response following the standard operation procedure. The Study suggested that we should train the officers in the district and sub district level and leaders in communi¬ties to be in charge of disease and event based surveillance in the community.